A study of governance practices in corporate foundations - Sérgio Ephim Mindlin (RAUSP: Revista de Administração da Universidade de São Paulo, 2012)
Implementation of social investments through corporate foundations is growing and, therefore, it is important to study their governance aspects better. Governance is conceptualized as a set of control and incentive mechanisms to overcome the so-called agency conflicts, which originate from the separation of property and management in for-profit organizations, a concept also applied to nonprofit institutions. It is argued that corporate foundations have the characteristics both of companies and of civil society organizations, which distinguishes them from both types of organizations. This paper analyses a study in which a set of governance mechanisms, adapted from those identified by a literature review of corporate and nonprofit governance, was selected for study. It is an exploratory descriptive case study, which analyzed data about eight organizations collected through publications and interviews with their CEOs. The data analysis indicates that it is appropriate to distinguish the different organization types and to apply the agency theory. Research results indicate that the selected governance mechanisms may be adapted and used in corporate foundations. However, they are only partially applied in the observed cases, which suggests the need for further studies that might consolidate these practices in such organizations.